2019
DOI: 10.1155/2019/3435901
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling Inhibition by Smoothened Antagonist BMS-833923 Reduces Osteoblast Differentiation and Ectopic Bone Formation of Human Skeletal (Mesenchymal) Stem Cells

Abstract: Background Hedgehog (Hh) signaling is essential for osteoblast differentiation of mesenchymal progenitors during endochondral bone formation. However, the critical role of Hh signaling during adult bone remodeling remains to be elucidated. Methods A Smoothened (SMO) antagonist/Hedgehog inhibitor, BMS-833923, identified during a functional screening of a stem cell signaling small molecule library, was investigated for its effects on the osteoblast differentiation of human skeletal (mesenchymal) stem cells (hMSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…Expression of SMAD4, which has a major role in regulating osteoblast viability and bone homeostasis 45 , was also significantly increased in hBMSCs treated with XAV-939. In addition, we identified TNF, NFκB, and STAT signaling among the top activated signaling pathways in XAV-939-treated hBMSCs; all are known to play a role in osteoblast differentiation and bone formation 29 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Expression of SMAD4, which has a major role in regulating osteoblast viability and bone homeostasis 45 , was also significantly increased in hBMSCs treated with XAV-939. In addition, we identified TNF, NFκB, and STAT signaling among the top activated signaling pathways in XAV-939-treated hBMSCs; all are known to play a role in osteoblast differentiation and bone formation 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Small molecule inhibitors targeting intracellular signaling pathways have been employed as chemical tools to determine the molecular mechanisms controlling stem cell proliferation and differentiation 25 , 30 . Our group has employed this chemical biology approach to identify a number of molecular targets and pathways that are important for osteoblast and adipocyte differentiation of hMSCs 25 , 27 29 , 31 , 34 , 35 . In the current study, we identified XAV-939 small molecule inhibitor, during small molecule library functional screen, as an enhancer of osteoblast differentiation of hMSCs 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the induction of BMP2 and PTCH expression in undifferentiated SDC-1 KD cultures suggests the BMP and SHH signalling pathways are activated. BMP2 is a predominantly pro-osteogenic factor for hMSCs [44,45] and SHH signalling is also required for hMSC osteogenic differentiation [46,47]. When undifferentiated SDC-1 KD cultures were differentiated, these cultures appeared to have enhanced osteogenic differentiation, with increased von Kossa and Alizarin Red staining.…”
Section: Discussionmentioning
confidence: 99%